Skeletal arsenic of the pre-Columbian population of Caleta Vitor, northern Chile. (June 2015) - Swift, Jaime; Cupper, Matthew L.; Greig, Alan; Westaway, Michael C.; Carter, Chris; Santoro, Calogero M.; Wood, Rachel; Jacobsen, Geraldine E.; Bertuch, Fiona
Abstract: Exposure to toxic arsenic has severe health consequences for past and present societies. This research resolves changes in a pre-Industrial population's exposure to the toxin within an arsenic-endemic area of the Atacama Desert of northern Chile over long timescales. Inductively coupled plasma mass spectrometry (ICP-MS) trace element analysis of human bone and tooth samples from 21 burials at Caleta Vitor on the Pacific coast of northern Chile has established that the pre-Columbian inhabitants were exposed to elevated levels of arsenic where one third of the sample population had accumulated levels in their skeletal system indicative of chronic poisoning. Coupled with new accelerator mass spectrometry (AMS) radiocarbon ages for the skeletal samples, spanning c. 3867 to 474 cal BP and encompassing all major cultural periods of the region, these results demonstrate the continual risk of arsenic poisoning over several millennia of occupation at one site. Numerous factors may have partially contributed to the population's inferred poisoning, due to the complex interaction of various environmental sources of arsenic and human behaviours. Increased exposure to arsenic could relate to climatic variability influencing sources of drinking water or anthropogenic activities such as mining and metallurgy or dietary changes associated with agriculture. Assessment of these potential sources of arsenic toxication, including evaluation of modern environmental data from the region, suggests contaminated drinking water was the most likely cause of arseniasis. Highlights: Late Chinchorro to Inka Chilean skeletal remains were tested for elevated arsenic. Our work is the first to examine arseniasis in all cultural periods for the region. One-third of the population suffered from chronic poisoning. AMS radiocarbon ages confirm a continual risk of poisoning over several millennia. Contaminated drinking water was the most likely cause of poisoning.